Persistence of submerged macrophytes in a drying world: Unravelling the timing and the environmental drivers to produce drought‐resistant propagules - Calero, Sara; Morellato, Leonor Patrícia C.; Rodrigo, María A. (Aquatic conservation, 2018)
Under a warming scenario many permanent inland water bodies in the Mediterranean region have become temporary ones, so the persistence of submerged macrophytes depends on the timely production of drought‐resistant propagules. Phenological research measures the timing of ecological processes and allows the consequences of disturbances such as climate change to be evaluated. Among macrophytes, the charophytes are widely distributed benthic macroalgae and are particularly sensitive to environmental variations. The systems in which they live constitute valuable, threatened, and protected habitats (European Habitats Directive code 3140). This study established a methodological basis for determining which environmental drivers trigger the sexual reproductive phenology of charophytes. For the first time, circular statistics were applied to describe and compare seasonal patterns for submerged macrophytes. Over a period of 2 years, three charophyte species growing in two Mediterranean brackish ponds were monitored. Most of the sexual reproduction occurred during spring and summer, including the production of drought‐resistant propagules, before the harshest conditions arrived. Each species showed a distinctive phenological pattern, according to specific breeding systems, life cycles, and environmental tolerances and requirements. Deeper conditions and higher salinities delayed reproduction. Different rainfall intensities in autumn produced distinctions between years, as stronger rainfall reduced the salinity stress and stimulated the reproduction of plants. Interacting factors act as cues for charophyte reproduction and cause antagonistic effects on propagule production. Among them, the heat required for each phenophase peak is essential for understanding the phenology of a population and for predicting its long‐term persistence. Charophytes appear to be good candidates for tracking climate change in shallow ecosystems. Further phenological studies should consider more species, populations, and long‐term observations in order to predict climate‐change effects on water bodies, and to develop effective plans for management and conservation. Circular statistics is a potential tool for analysing phenology in the context of global warming, as well as for many other conservation issues.